Rancang Bangun Modulator FM - David Satria Efendi; Febrizal Febrizal; Rahyul Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
FM modulator is a device used for the modulation process. Modulation is a process to lay the information signal on carrier signal for reduce interference and noise when signal ispropagated. The information signal has 3,4 KHz in frequency , and will be modulated with 19 KHz (carrier signal). FM modulator is designed with PLL (Phase Locked Loop) method, itused the concept of phase signal locking . FM modulator with PLL method consist of four blocks, that is oscillator colpitt, phase comparator, second orde LPF butterworth and VCOwienbridge. Design of FM modulator trainer begins with calculate to determine the component value which suitable with cut off frequency. The next process to make the layoutof the pcb board, dissolution layout, pcb board drilling, mounting the female connectors to pcb board, installation of component connectors to the header, and make a box to placetrainer FM demodulator. The results obtained at each signal fm demodulator block is different. The modulated signal is obtained at the VCO wienbridge.Keywords : FM Modulator, Modulated Signal, Phase Locked Loop, Carrier Signal,Information Signal.